Nurses' families' experiences of involvement in nursing errors: A qualitative study - Zahra Mokhtari; Mohammadali Hosseini; Hamidreza Khankeh; Masoud Fallahi-Khoshknab; Alireza Nikbakht Nasrabadi (Elsevier, 2019)
Background: The most important and irreversible consequence of medical errors is the human impact caused by unintended actions. In a few studies, the significant impact of this error on the private life of healthcare staff have been mentioned, but the problems of the involved nurses' families had been ignored, as of now. Aims: This study aimed to explain the nurses' families' experiences of involvement in nursing errors. Methods: This is a qualitative study using conventional content analysis with 20 semi-structured interviews conducted with nurses and family members of nurses involved in medical errors, done through purposeful sampling and willingness to participate in the study. Results: The results of the data analysis consisted of five main categories including disruption in family functioning, the crisis of fear, oppression, damage, and neglect, along with 15 subcategories. Conclusion: Considering the effects of nursing errors on the families of nurses involved in the error, such as disruption of family functioning, the family of nurses involved in the error should also be considered and paid attention to. These families are abandoned and the need to promote the culture of supporting the family is tangible. Keywords: Family, Neglected victim, Nurses, Medical error, Qualitative research